US Intervention in Nicaragua - Garcia, Edmundo G. (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Under the pretense that the U.S. is looking out for it's own national security, it has continuously hindered Nicaragua's chance at an authentic national democratic government of its own. Through the creation and support of almost a half-century long dictatorship that left the poor nation in shambles, as well as economic sabotage, arming and supporting the "contras" or remnant supports of the previous dictatorship, and the setting up of military installations in the region, the US has persistently interfered with Nicaragua's strive for democracy. Under the leadership of the Sandinistas, Nicaragua must uphold significant principles such as non-intervention, self-determination, collective self-defense, the peaceful settlement of disputes, and the advocating of human rights and democracy to work towards the self-governance and independence they seek to achieve. Furthermore, the United States would benefit with the realization that, because of their unwanted pursuit and interventions, they have lost their own fundamental principle, which, in the first place, was responsible for its own emergence: the people's rights to self-determination.
Keywords: Nicaragua, United States intervention, Sandinistas, Somoza, Ronald Reagan, self-determination